Systematic Review and Meta-analysis of Current Experience in Treating IPNB: Clinical and Pathological Correlates. Issue 4 (April 2016) - Gordon-Weeks, Alex N.; Jones, Keaton; Harriss, Elinor; Smith, Adrian; Silva, Michael
Abstract : Objective: To systematically review studies reporting clinicopathological features of intraductal papillary neoplasm of the bile duct (IPNB) to provide evidence-based guidance for management. Background: IPNB is a rare tumor type. Management decisions are currently based upon anecdotal evidence and small case series. To data, there has been no systematic review of IPNB literature. Methods: MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews were searched and data were extracted from relevant studies. Meta-analysis was used to pool study estimates. Evidence of association was determined by comparing pooled crude odds ratios (OR) derived from abstracted data. Results: Fifty-seven retrospective case series were included. At least 43% of 476 specimens contained invasive disease. Invasive tumors were found at significantly higher frequency in pancreaticobiliary than intestinal, gastric or oncocytic-type IPNB [pooled OR 2.5, 95% confidence interval (CI) 1.5–4.2, P < 0.001]. A significantly higher proportion of pancreaticobiliary tumors compared with intestinal tumors expressed MUC-1 [86.4% (95% CI 75.1%–94.7%) vs 13.2% (95% CI 4.6%–25.2%), respectively P < 0.001]. IPNB identified in centers from Asia were more likely to be intrahepatic and were less frequently invasive compared with those from Western centers. Pooled estimates of absolute survival after IPNB resection were 96% (95% CI 93%–99%) at 1 year, 79% (95% CI 69%–88%) at 3 years, and 65% (95% CI 46%–76%) at 5 years. Conclusions: Early surgery is advisable for radiologically suspected IPNB as it is frequently invasive. The pathobiology of IPNB demonstrates geographic variation. Pancreaticobiliary IPNB expresses MUC1 and is more frequently associated with invasive disease than other IPNB subtypes.